L-Carnitine ameliorates methotrexate-induced oxidative organ injury and inhibits leukocyte death - YEGEN, BERRAK; ERCAN, FERİHA; ŞENER, GÖKSEL; ŞİRVANCI, SERAP (SPRINGER, 2006)
Methotrexate (MTX), a folic acid antagonist widely used for the treatment of a variety of tumors and inflammatory diseases, affects normal tissues that have a high rate of proliferation, including the hematopoietic cells of the bone marrow and the gastrointestinal mucosal cells. To elucidate the role of free radicals and leukocytes in MTX-induced oxidative organ damage and the putative protective effect of L-carnitine (L-Car), Wistar albino rats were administered a single dose of MTX (20 mg/kg) followed by either saline or L-Car (500 mg/kg) for 5 days. After decapitation of the rats, trunk blood was obtained, and the ileum, liver, and kidney were removed for histological examination and for the measurement of malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity, and collagen content. Our results showed that MTX administration increased the MDA and MPO activities and collagen content and decreased GSH levels in all tissues, while these alterations were reversed in L-Car-treated group. The elevated serum TNF-alpha level observed following MTX treatment was depressed with L-Car. The oxidative burst of neutrophils stimulated by Annexin V was reduced in the saline-treated MTX group, while L-Car abolished this inhibition. Similarly, flow cytometric measurements revealed that leukocyte apoptosis was increased in MTX-treated animals, while L-Car reversed these effects. Severe degeneration of the intestinal mucosa, liver parenchyma, and glomerular and tubular epithelium observed in the saline-treated MTX group was improved by L-Car treatment. These results suggest that L-Car, possibly via its free radical scavenging and antioxidant properties, ameliorates MTX-induced oxidative organ injury and inhibits leukocyte apoptosis. Thus, supplementation with L-Carnitine as an adjuvant therapy may be promising in alleviating the systemic side-effects of chemotherapeutics.
Keywords: methotrexate; myeloperoxidase; glutathione; TNF-alpha; apoptosis; oxidative injury; ACETYL-L-CARNITINE; INDUCED LIPID-PEROXIDATION; L-PROPIONYL-CARNITINE; SMALL-INTESTINE; HEMODIALYSIS-PATIENTS; RENAL-FAILURE; RAT MODEL; HEPATOTOXICITY; INFLAMMATION; GLUTATHIONE